The U.P. College of Engineering Library an analysis of the usage patterns and attitudes of engineering students towards its resources, facilities and services - Bamba, Rosemarie N. (1976)
This is a study of the usage patterns and attitudes of students in the UP College of Engineering during the second semester, 1974-75, towards the resources, facilities and services available in the college library. Ten percent (10 percent) of the total college enrolment (1,096) were taken as repondents to the questionnaires which were administered during the survey. A total of 116 questionnaires were distributed, out of which 112 were returned. Processing of gathered data was computerized and analysis of relationships between variables was made through the use of frequency distribution, cross-tabulations and chi-square tests.